Analisis Infektivitas Simian-Human Immunodeficiency Virus pada Peripheral Blood Mononuclear Cell Macaca fascicularis dan M. nemestrina Secara In Vitro - Darmono, Gede Eko; Triwidyaningtyas, Silvia; Bela, Budiman; Iskandriati, Diah; Sajuthi, Dondin; Pamungkas, Joko (Jurnal Veteriner, 2022)
Development of human immunodeficiency virus type 1 (HIV-1) vaccines and anti-retroviral treatmentis currently hindered by the lack of models representing prominent symptoms of HIV-1 infections seen in humans. Simian-human immunodeficiency virus (SHIV) was constructed to resolve the limitations of SIVmac model and has been used in nonhuman primate model ofviral infections, particularly infections by the close relatives of HIV-1. Macaca fascicularis and M. nemestrina are being developed as model HIV/AIDS, by using chimeric virus SHIV produced by replacing the nucleotide structure of cyclophilin A binding region, vif gene and nef of HIV-1 with cyclophilin A binding region, vif gene and nef from SIV. The research aims to study the model of HIV/AIDS on nonhuman primates PBMC in vitro using SHIV. In particular, the study aims to obtain information about the capability of SHIV replication in PBMC of M. fascicularis and M. nemestrina. Results showed a cytopathic effect (CPE) in the form of multinucleated giant cells and expression of p24 protein in PHA-stimulated PBMC cultures of M. fascicularis and M. nemestrina after SHIV infection. The conclusion of this study is that SHIV can infect PBMC M. fascicularis and M. nemestrina in vitro based on CPE and expression of p24 protein.